Orbit of the OJ287 black hole binary as determined from the General Relativity centenary flare - Valtonen, Mauri; Gopakumar, Achamveedu; Mikkola, Seppo; Zola, Staszek; Ciprini, Stefano; Matsumoto, Katsura; Sadakane, Kozo; Kidger, Mark; Gazeas, Kosmas; Nilsson, Kari; Berdyugin, Andrei; Piirola, Vilppu; et al. (AAS/Division of Dynamical Astronomy Meeting #47, 2016)
OJ287 goes through large optical flares twice each 12 years. The times of these flares have been predicted successfully now 5 times using a black hole binary model. In this model a secondary black hole goes around a primary black hole, impacting the accretion disk of the latter twice per orbital period, creating a thermal flare. Together with 6 flares from the historical data base, the set of flare timings determines uniquely the 7 parameters of the model: the two masses, the primary spin, the major axis, eccentricity and the phase of the orbit, plus a time delay parameter that gives the extent of time between accretion disk impacts and the related optical flares. Based on observations by the OJ287-15/16 Collaboration, OJ287 went into the phase of rapid flux rise on November 25, on the centenary of Einstein’s General Relativity, and peaked on December 5. At that time OJ287 was the brightest in over 30 years in optical wavelengths. The flare was of low polarization, and did not extend beyond the optical/UV region of the spectrum. On top of the main flare there were a number of small flares; their excess brightness correlates well with the simultaneous X-ray data. With these properties the main flare qualifies as the marker of the orbit of the secondary going around the primary black hole. Since the orbit solution is strongly over-determined, its parameters are known very accurately, at better than one percent level for the masses and the spin. The next flare is predicted to peak on July 28, 2019.Detailed monitoring of this event should allow us to test, for the first time, the celebrated black hole no-hair theorem for a massive black hole at the 10% level. The present data is consistent with the theorem only at a 30% level. The main difficulty in observing OJ287 from Earth at our predicted epoch is its closeness to the sun. Therefore, it is desirable to monitor OJ287 from a space-based telescope not in the vicinity of Earth. Unfortunately, this unique opportunity for testing the above celebrated theorem of General Relativity using OJ287 will not be available again until after several orbital cycles.The full list of participants in the OJ287-15/16 Collaboration is found in ApJL 819, L37, 2016.